Accuracy and precision of abdominal diameter measurement by a new instrument - A Thamprasit; W Setasuban; S Soonthornpun (Journal of Health Science and Medical Research (JHSMR), 2005)
Objective: To study the accuracy and precision of abdominal diameter measurement of a new instrument. Material and Methods: Nineteen healthy volunteers (15 men and 4 women) aged 20-44 year and median body mass index of 22.0 kg/m2 (range 18.8-36.8) were studied. The sagittal and transverse abdominal diameter were measured by the computed tomography scan and the new instrument on the same occasion. Results: There was a good correlation between the abdominal diameters measured by the new instrument and those measured by the computed tomography scan with correlation coefficient of 0.95 for sagittal abdominal diameter and 0.99 for transverse abdominal diameter. The mean difference+SD of the differences of the sagittal and transverse abdominal diameter measured by the new instrument and those by the computed tomography scan were 0.67+0.81 cm and -0.89+0.63 cm, respectively. Conclusion: This new instrument has good accuracy and precision in measuring the abdominal diameters.